1997
DOI: 10.1006/jsre.1997.5223
|View full text |Cite
|
Sign up to set email alerts
|

Sulfo-LewisXDiminishes Neutrophil Infiltration and Free Radicals with Minimal Effect on Serum Cytokines after Liver Ischemia and Reperfusion

Abstract: cytes. One mechanism of accumulation is cell adhesion. Background: Cell adhesion plays a central role in The selectin family of adhesion molecules play a pivotal the pathogenesis of neutrophil-induced hepatic injury role in the leukocyte/endothelial cell events associated after ischemia and reperfusion. Sialyl Lewis x binds to with tissue inflammation and damage following ischselectins mediating neutrophil adherence to endothe-emia and reperfusion (I/R) [1][2][3][4]. Previous in vitro and lium, thereby facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Through this, it prevents the formation of OH − radicals, which are more toxic. Criado found that CAT enzyme levels increased in 30 minutes after I/R damage (47). For GPx catalyses H 2 O 2 and lipid hydroperoxidase, it protects to cellular membranes from damage, prevents the start and development of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Through this, it prevents the formation of OH − radicals, which are more toxic. Criado found that CAT enzyme levels increased in 30 minutes after I/R damage (47). For GPx catalyses H 2 O 2 and lipid hydroperoxidase, it protects to cellular membranes from damage, prevents the start and development of lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are mainly responsible for the physiopathological changes that occur after ischemia-reperfusion injury [1][2][3] . These cells are markedly activated when the ischemically damaged liver is transplanted.…”
Section: Introductionmentioning
confidence: 99%
“…En nuestro estudio, la menor expresión detectada en ICAM-1, VCAM-1 y PECAM-1 determinará una menor interacción leucocito-endotelio y consecuentemente una menor infiltración neutrofílica, aspecto éste directamente relacionado con el daño en la respuesta inflamatoria; a su vez la menor activación e infiltración neutrofílica conducirá a una menor producción de radicales libres del oxígeno causantes de lesión tisular, éstos a su vez, como mediadores inflamatorios de primer orden, tienen la capacidad de activar factores transcripcionales como NFκB responsable, como vimos en apartados anteriores, de la producción de diferentes citocinas proinflamatorias como el TNF-α, la IL-1 y el INF-γ responsables del incremento de la expresión de CAMs (295) y en el caso del TNF-α del incremento de producción de RLO. Todo ello redundará en una menor lesión tisular con un mantenimiento de la función del órgano y consecuentemente una menor morbi-mortalidad (70,95,97,277) .…”
Section: En Ambos Casos Comprobamos Cómo El Grupounclassified